2005
DOI: 10.1080/0028825x.2005.9512946
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical study of growth ofPhormiumvarieties used for traditional Maori weaving

Abstract: Twelve Maori weaving varieties of Phormium were grown at 11 widely separated sites in New Zealand in an experiment involving participation of weavers, teachers, and students. Leaf dieback and leaf appearance during establishment and growth of leaf length and blade width, shoot production, and expansion of plant basal circumference over 4-7 years were recorded. Observations were made on factors, particularly cold, that caused plant damage. Data were analysed to test for site × variety interaction. The sites pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 9 publications
0
42
0
Order By: Relevance
“…Ramet formation for plants raised from seed is slow, with estimations of up to 15 ramets after 3 years (Poole 1940). Harris et al (2005) found that ramet number varied significantly with cultivar type: Maeneene, for example, produced ramets at a faster rate, with around 134 ramets likely after 3 years. Ramets mature in 3-6 years to produce inflorescences and then senesce after flowering (Poole 1940).…”
Section: Vegetative Reproductionmentioning
confidence: 98%
See 4 more Smart Citations
“…Ramet formation for plants raised from seed is slow, with estimations of up to 15 ramets after 3 years (Poole 1940). Harris et al (2005) found that ramet number varied significantly with cultivar type: Maeneene, for example, produced ramets at a faster rate, with around 134 ramets likely after 3 years. Ramets mature in 3-6 years to produce inflorescences and then senesce after flowering (Poole 1940).…”
Section: Vegetative Reproductionmentioning
confidence: 98%
“…Certainly, wild P. tenax shows an array of morphological forms which appear to be related to habitat features such as soil fertility. To investigate the contributions of genetic and phenotypic variability, 12 Maori cultivars were chosen for a replicated growth experiment using clones at 11 different sites from kaitaia to otago (Harris et al 2005). The sites were chosen to cover a wide range of conditions relating to climate, latitude, soil fertility, and water availability, and clones of each cultivar were planted at each site.…”
Section: Intraspecific and Interspecific Variationmentioning
confidence: 99%
See 3 more Smart Citations